(untitled) (Parliamentary Studies, 2012)
The article examines commemorative speeches given at March 11 celebrations in the Seimas of the Republic of Lithuania by the Seimas chairmen of the first decade of independence Vytautas Landsbergis and Česlovas Juršėnas. March 11 is a special celebration of Lithuania, however orators move behind festive rhetoric, they talk about the past and present, today’s political realities of the country, refer to the most important achievements and sores of the year, discuss domestic and foreign policy, promote specific actions of the members of the Seimas. From the linguistic expression of famous personalities analyzed, their positions, goals, objectives and understanding of assumed obligations and responsibilities are evident. The main goal of the political speeches is to persuade the addressee with rational arguments of what is spoken. Despite the differences of the rhetorical expression, one or two right-wing leader’s remarks to the left-wing, and left-wing’s remarks to the right-wing, both orators in their speeches form and emanate ideals and values close to universal audience, raise questions of victimization, draws the same direction of geopolitical orientation of Lithuania.